2019
DOI: 10.3748/wjg.v25.i31.4343
|View full text |Cite
|
Sign up to set email alerts
|

Common features between neoplastic and preneoplastic lesions of the biliary tract and the pancreas

Abstract: the bile duct system and pancreas show many similarities due to their anatomical proximity and common embryological origin. Consequently, preneoplastic and neoplastic lesions of the bile duct and pancreas share analogies in terms of molecular, histological and pathophysiological features. Intraepithelial neoplasms are reported in biliary tract, as biliary intraepithelial neoplasm (BilIN), and in pancreas, as pancreatic intraepithelial neoplasm (PanIN). Both can evolve to invasive carcinomas, respectively chola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 159 publications
(143 reference statements)
0
23
0
Order By: Relevance
“…The malignant forms of CC and PDAC arise from their pre-malignant counterparts; namely, biliary intraepithelial neoplasia and pancreatic intraepithelial neoplasia [5] . The molecular and phenotypical similarity between extrahepatic CCs and PDAC is likely to be related to their shared embryological origin, with both the proximal pancreatic and distal biliary ducts arising from a common endodermal structure: the ventral foregut [15] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The malignant forms of CC and PDAC arise from their pre-malignant counterparts; namely, biliary intraepithelial neoplasia and pancreatic intraepithelial neoplasia [5] . The molecular and phenotypical similarity between extrahepatic CCs and PDAC is likely to be related to their shared embryological origin, with both the proximal pancreatic and distal biliary ducts arising from a common endodermal structure: the ventral foregut [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The 2 most common mutations implicated in the carcinogenesis of PDAC (p53 and KRAS) have been found to play a similar role in the progression of biliary intraepithelial neoplasias to CCs [16 , 17] . Unsurprisingly, both share a similar growth pattern, are poorly responsive to conventional chemotherapy and are seldom associated with a good prognosis [5 , 15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on recent evidence that in adult human pancreatic duct glands (PDGs), distinct niches of progenitor cells constitute a natural source of β cells for the purposes of regenerative medicine [42][43][44] and that PDGs might have a central role in the development of PDAC [45], human biliary tree stem/ progenitor cells and PDAC-derived cell lines were used to assess whether ATRA induces the differentiation of both cell systems towards a pancreatic islet fate by up-modulating the expression of Vav1.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous preclinical studies have indicated other surface markers potentially useful to identify or target CSCs: CD90, ALDH, CD47, CD44, CD24, microtubule-associated doublecortin-like kinase 1 (DCLK1) that are expressed in multiple cancer types with a higher expression in CSCs compared to other bulk tumor cells [ 82 , 97 , 106 , 107 ]. DCLK1 has been described as a CSC associated antigen in colon, pancreatic [ 108 , 109 , 110 ] and even in Cholangiocarcinoma (CCA) tumors [ 111 ]. Recently, preclinical findings supported promising results with adoptive immunotherapy based on DCLK1-CAR T lymphocytes against colorectal cancer (CRC) [ 107 ].…”
Section: Cellular Immunotherapy Targeting Cscsmentioning
confidence: 99%